5G Arrives - Gregory, Mark A (Journal of Telecommunications and the Digital Economy, 2018)
Papers in the December 2018 issue of the Journal include discussion on 5G security, what’s next for the National Broadband Network, a technical paper on the conflicts in routing and UAV autonomy, HTTP traffic flow load balancing and an insight into how the use of location information affects privacy. The history of Australian telecommunications paper on impressions of an overseas visit by a lines engineer provides an insight into how knowledge transfer improves with the opportunity to study telecommunications in Europe, North America and Australia. The Journal welcomes contributions.